The Effect of Integrating Mobile Application in Language Learning: An Experimental Study - Mengorio, Trixie Mae; Dumlao, Remart (JET (Journal of English Teaching), 2019)
Innovation in Language Teaching Methodology should address the needs and demands of the 21st century learners and the birth of Mobile Aided Language Learning created abundant possibilities for the field of language education. This study investigates the effect of the Mobile Application: Moodle in teaching ESL learners. A quasiexperimental research with 100 respondents in Junior High School at Rizal Technological University-Laboratory High School of the Academic Year 2017-2018. The research data were gathered from the pre-test and post-test results during the betatesting activity and Focus Group Discussion conducted among the experimental set during the 4th grading period. Experimental Set used the Mobile Application: Moodle in their daily classroom discussion and activity tasks. Results shows that there is an increase with the performance of the Experimental Group compared to the Controlled Group test results. Also, the students in the experimental set express positive feedback about the integration of Mobile App in teaching and learning process. The study suggests that with further research and development of the program, it will enhance the possibility of MALL acquisition in teaching ESL Keywords: mobile aided language learning (MALL); e-learning; m-learning; mobile applications